Reactions of o-aminothiophenol and o-aminophenyl disulfide with itaconic anhydride and (-)-dimenthyl itaconate: access to enantiomerically pure 1,5-benzothiazepines and benzothiazolyl-2-methylacrylic acid - Baag, Md. Merajuddin; Sahoo, Manoj Kumar; Puranik, Vedavati G.; N. P. Argade (Synthesis-Stuttgart, 2007)
{A facile chemo- and regioselective reactions of o-aminothiophenol (o-ATP) with itaconic anhydride is described. 1,5-Benzothiazepinyl-3-acetic acid is obtained in 81% yield via the exclusive Michael type addition of the thiol unit from o-ATP to the carbon-carbon double bond in itaconic anhydride followed by an intramolecular anhydride ring opening with an amine unit. The moderately stereoselective Michael type addition of the thiol unit from o-ATP to (-)-dimenthyl itaconate to obtain a mixture of diastereomers in a 7:3 ratio in 82% yield has been demonstrated. The reductive sulfur-sulfur bond cleavage in the dicarboxylic acid, 2({2-[2-(3-carboxybut-3-enoylamino)phenyidisulfanyl]phenylcarbamoyl\
Keywords: Magnetic nanoparticles; magnetic properties; spin glasses

Easy access to alpha-aryl substituted gamma-ketophosphonates: lewis acid mediated reactions of 1,3-diketones with alpha-hydroxyphosphonates and tandem regioselective C-C bond cleavage - Pallikonda, Gangaram; Chakravarty, Manab; Sahoo, Manoj Kumar (Organic & Biomolecular Chemistry, 2014)
A range of alpha-aryl substituted gamma-ketophosphonates is synthesised by Lewis acid mediated reactions of 1,3-diketones and easily accessible, inexpensive benzylic alpha-hydroxyphosphonates in an operationally simple method under solvent-free conditions without exclusion of air/moisture. A regioselective C-C bond cleavage for 1,3-diketones in a tandem fashion has also been demonstrated. Synthesis of a gamma-ketophosphonate with phenol functionality at the a-position (structural analogue of raspberry ketone, a natural product) has also been presented.

Reversed reactivity of anilines with alkynes in the rhodium-catalysed C-H activation/carbonylation tandem - Midya, Siba Prasad; Sahoo, Manoj Kumar; Landge, Vinod Gokulkrishna; Rajamohanan, P. R.; Balaraman, Ekambaram (Nature Communications, 2015)
Development of multicatalytic approach consisting of two or more mechanistically distinct catalytic steps using a single-site catalyst for rapid and straightforward access of structurally complex molecules under eco-benign conditions has significance in contemporary science. We have developed herein a rhodium-catalysed C-H activation strategy which uses an unprotected anilines and an electron-deficient alkynes to C-C bonded products as a potential intermediate in contrast to the archetypical C-N bonded products with high levels of regioselectivity. This is followed by carbonylation of C-H bond activated intermediate and subsequent annulation into quinolines has been described. This rhodium-catalysed auto-tandem reaction operates under mild, environmentally benign conditions using water as the solvent and CO surrogates as the carbonyl source with the concomitant generation of hydrogen gas. The strategy may facilitate the development of new synthetic protocols for the efficient and sustainable production of chemicals in an atom-economic way from simple, abundant starting materials.

Reverse-hydroformylation: a missing reaction explored - Nandakumar, Avanashiappan; Sahoo, Manoj Kumar; Balaraman, Ekambaram (Organic Chemistry Frontiers, 2015)
Recent progress in transition-metal catalysed acceptor- and acceptorless-reverse hydroformylation of aldehydes for the conversion of olefins has been discussed. The aldehyde feedstock serves as a source for production of syngas and valuable alkenes.

Well-defined palladium(II) complexes for ligand enabled C(sp3)-alkynylation - Landge, Vinod Gokulkrishna; Sahoo, Manoj Kumar; Midya, Siba Prasad; Jaiswal, Garima; Balaraman, Ekambaram (Dalton Transactions, 2015)
The first example of ligand-enabled C(sp3)-alkynylation of 8-methylquinoline is reported. The reaction is catalysed by well-defined Pd(II) complexes. The present C(sp3)-alkynylation has a broad substrate scope as well as functional group tolerance and proceeds efficiently under mild conditions.

Nickel-catalyzed direct alkynylation of C(sp2)-H bonds of amides: an “inverse sonogashira strategy” to ortho-alkynylbenzoic acids. just accepted - Landge, Vinod Gokulkrishna; Shewale, Chinmay H.; Jaiswal, Garima; Sahoo, Manoj Kumar; Midya, Siba Prasad; Balaraman, Ekambaram (Catalysis Science & Technology, 2016)
Nickel-catalyzed direct alkynylation of C(sp2)–H bonds of amides using commercially available, inexpensive 8-aminoquinoline as a removable bidentate directing group is described. The present ortho-alkynylation has a broad substrate scope, functional group tolerance and high regiocontrol, and can be scaled up. The efficiency and selectivity of this strategy provide sustainable routes to a diverse array of ortho-alkynylbenzoic acids under Ni(II)-catalyzed conditions.